The 1975 Icelandic ‘Women’s day off’ in Nordic print media - Kurvinen, Heidi; Pálmadóttir, Valgerður (Routledge, 2025)
In October 1975, the Icelandic women’s movement organized a ‘Women’s Day Off’ (WDO), a one-day strike designed to reveal the societal importance of women’s work. In this article, we explore media coverage of the WDO in the Nordic countries. Through an analytical lens that focuses on media framing and journalistic practices, we analyse differences in the coverage’s scope and content. We also contextualize the coverage against the background of sociopolitical factors that may have affected the cultural filtering of the news, as well as journalistic practices and resources in each country. In doing so, we demonstrate that the coverage relied on each newsroom’s estimation of the event’s newsworthiness for local readers. That news value was influenced by the country in question’s cultural proximity to Iceland, the state of local feminist organizing and public discussions regarding gender equality, and other news topics in circulation at the time. Our analysis is based on a reading of media texts related to the WDO that we gathered using digital interfaces of the national libraries of Norway, Denmark, Sweden and Finland, complemented by a manual search in cases where such digitization was lacking.